Estudos isotópicos (Pb, O, H, S) em zonas alteradas e mineralizadas do depósito cupro-aurífero Visconde, Província Mineral de Carajás - SILVA, Antonia Railine da Costa (Universidade Federal do Pará, 2015)
The Cu-AuVisconde deposit is located in the Carajás Mineral Province, northern Brazil, about 15 km east of the world-class Sossego deposit. It lies within a regional WNW–ESE-striking shear zone that marks the contact between the ~2.76 Ga metavolcano-sedimentary rocks of the Carajás Basin and the basement units. Other Cu- Au deposits with similar characteristics (Bacaba, Castanha, Alvo 118, Cristalino, Jatobá) occur along this shear zone. They have been included in the IOCG class, although much controversy exists regarding their genesis, particularly with respect to the mineralization age and source of fluids, ligands and metals. TheVisconde deposit is hosted by Archean rocks, mainly felsic metavolcanic rocks (2968 ± 15 Ma), the Serra Dourada granite (2860 ± 22 Ma), and gabbro/diorites. These rocks are variably sheared and reveal various types of hydrothermal alteration with strong structural control. The earliest types are the sodic (albite-scapolite) and sodic-calcic alterations (albiteactinolite ± tourmaline ± quartz ± magnetite ± scapolite ± epidote), which promoted ubiquitous replacement of the rock primary minerals and precipitaton of disseminated chalcopyrite, pyrite, molybdenite and pentlandite. Oxygen isotope data of representative minerals from these stages show that the hydrothermal fluids were hot (410 – 355°C) and 18O-rich (δ18OH2O = +4.2 to +9.4‰). The following potassic stage is characterized by intense biotitization of the rocks, which developed concomitantly a mylonitic foliation highlighted by the remarkable orientation of biotite flakes. This mica precipitated from fluids with similar oxygen isotope signature to that of the previous stages (δ18OH2O = +4.8 to +7.2‰, at 355°C). Microcline and allanite are other typical minerals of this stage, in addition to chalcopyrite that deposited along the foliation planes. At lower temperatures (230 ± 11°C), 18O-depleted fluids (δ18OH2O = -1.3 to +3.7‰) generated a calcic-magnesian mineral assemblage (albite + epidote + chlorite ± actinolite ± calcite) present mostly in veins and contemporaneous with the main mineralization. The δ18OH2O and δDH2O data indicate that the hydrothermal fluids were initially formed by metamorphic and formation waters, possibly with some contribution of magmatic water. At later stages, there was a considerable influx of surface water. The resulting fluid dilution and cooling might have accounted for the abundant precipitation of sulphides (chalcopyrite ± bornite ± chalcocite ± digenite) mainly in tectonic breccias, whose matrix contains up to 60% sulphides. These breccias represent the most important ore bodies, although sulphides also occur in veins together with sodic-calcic minerals. The mineral associations assign a Cu-Au-Fe-Ni-ETRL-B-P signature to the ore. The sulphur isotope composition (δ34SCDT= -1.2 to 3.4‰) is compatible with a magmatic source for sulphur, which could have been either exsolved from a crystallizing granitic magma or dissolved from sulphides originally present in preexisting igneous rocks. Additionally, it indicates relatively reducing conditions for the fluid. Dating of chalcopyrite by Pb leaching and total dissolution techniques yielded ages of 2736 ± 100 Ma and 2729 ± 150 Ma. Despite the large errors, they point to a Neoarchean age for the mineralization and preclude a Paleoproterozoic mineralizing event. The age of 2746 ± 7 Ma (MSDW = 4.9; Pb evaporation on zircon), obtained for a non-mineralized granitic intrusion present in the deposit area and correlated to the Planalto Suite, was considered as the minimum age for the mineralization. Thus, the Visconde deposit genesis could be related to the 2.76-2.74 Ga transpressive tectonothermal event that was responsible for the inversion of the Carajás basin and generation of granitic magmatism in the Carajás and Transition domains. Such an event should have triggered devolatilazion reactions in the Itacaiunas Supergroup rocks, producing metamorphic fluids or even driving off water trapped in the pores of the basin rocks. These fluids migrated along regional shear zones and reacted with both the basin and basement rocks through which they moved during the ductile regime. The subeconomic concentrations of the Visconde deposit might be the result of the absence of prominent structures that would otherwise favor a greater influx of fluids, as it seems to have been the case in the Sossego and Alvo 118 deposits.